2017
DOI: 10.4103/jomfp.jomfp_248_16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus16 DNA and p16INK4a protein in oral squamous cell carcinoma: A systematic review and meta-analysis

Abstract: Background and Aim:Indian patients with oral squamous cell carcinoma (OSCC) are etiologically associated with the use of tobacco and alcohol; yet, a proportion of tumors that may harbor human papillomavirus (HPV) infections cannot be neglected. The following meta-analysis was conducted to address the association of p16INK4a and HPV DNA with OSCC. In addition, the study also provides the updated prevalence of HPV-induced OSCC.Materials and Methods:Literature survey was performed using databases such as PubMed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…As we expected, salivary HPV16 showed a higher prevalence in oropharyngeal cancer (39.6%) than oral cancer (18.6%), in accordance with previous studies [37,39,40]. In particular, the salivary HPV16 prevalence in our study was slightly higher in oral cancer than reported in a meta-analysis by Nydiae et al [37] (18.6% vs 14.9%), however, other authors have reported higher rates of HPV16 prevalence in oral carcinoma, ranging from 20% to 50% [41][42][43]. Salivary HPV18 was another oncogenic HPV type commonly evaluated by the included studies.…”
Section: Discussionsupporting
confidence: 90%
“…As we expected, salivary HPV16 showed a higher prevalence in oropharyngeal cancer (39.6%) than oral cancer (18.6%), in accordance with previous studies [37,39,40]. In particular, the salivary HPV16 prevalence in our study was slightly higher in oral cancer than reported in a meta-analysis by Nydiae et al [37] (18.6% vs 14.9%), however, other authors have reported higher rates of HPV16 prevalence in oral carcinoma, ranging from 20% to 50% [41][42][43]. Salivary HPV18 was another oncogenic HPV type commonly evaluated by the included studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, a higher incidence of oral cancer is observed in South‐East Asia, likely attributed to excessive use of tobacco. The ratio of males to females diagnosed with oral cancer in India has been reported to be 2:1, indicating a higher occurrence among males . It is estimated that there are approximately 48 330 new cases and 9570 deaths due to oral cancer in the US annually.…”
Section: Introductionmentioning
confidence: 99%
“…In which, 32 studies have shown deep association of HPV with OPSCC and OSCC, of which 14 studies seemed to be significantly positive; these studies have shown that the prevalence of HPV in India varies across depending on the lifestyle differences and geographic regions; there is an increased HPV association in OPSCC and OSCC in South India than the Western and Eastern parts of India. [3161718] Apart from geographic location, the incidence of HPV-induced OPSCC also varies with the genotype of virus. polymerase chain reaction (PCR) was a commonly used test, and it has been proved to be more sensitive in detection of HPV in OPSCC, than IHC and in situ hybridization (ISH).…”
Section: Discussionmentioning
confidence: 99%
“…HPV is an epitheliotropic, nonenveloped virus of Papillomaviridae family with double-stranded circular DNA genome. [321] Autonomous, specific, and strong carcinogenic effect of HPV is difficult to justify. Unprotected and erratic sexual behavior has a high risk of incidence of HPV, especially in younger age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation